Possible Misdiagnosis of HIV associated Lymphoma as Tuberculosis among Patients attending Uganda Cancer Institute - Buyego, Paul; Nakiyingi, Lydia; Ddungu, Henry; Walimbwa, Stephen; Nalwanga, Damalie; Reynolds, Steven J.; Parkes‑Ratanshi, Rosalind (AIDS research and therapy, 2017)
Early diagnosis of HIV associated lymphoma is challenging because the definitive diagnostic procedure of biopsy, requires skills and equipment that are not readily available. As a consequence, diagnosis may be delayed increasing the risk of mortality. We set out to determine the frequency and risk factors associated with the misdiagnosis of HIV associated lymphoma as tuberculosis (TB) among patients attending the Uganda Cancer Institute (UCI). A retrospective cohort study design was used among HIV patients with associated lymphoma patients attending the UCI, Kampala, Uganda between February and March 2015. Eligible patient charts were reviewed for information on TB treatment, socio-demographics, laboratory parameters (Hemoglobin, CD4cells count and lactate dehydrogenase) and clinical presentation using a semi structured data extraction form. A total of 183 charts were reviewed; 106/183 were males (57.9%), the median age was 35 (IQR, 28–45). Fifty six (30.6%) patients had a possible misdiagnosis as TB and their median time on TB treatment was 3.5 (1–5.3) months. In multivariate analysis the presence of chest pain had an odd ratio (OR) of 4.4 (95% CI 1.89–10.58, p < 0.001) and stage III and IV lymphoma disease had an OR of 3.22 (95% CI 1.08–9.63, p < 0.037) for possible misdiagnosis of lymphoma as TB. A high proportion of patients with HIV associated lymphoma attending UCI are misdiagnosed and treated as TB. Chest pain and stage III and IV of lymphoma were associated with an increased risk of a possible misdiagnosis of lymphoma as TB.
Keywords: Misdiagnosis; Tuberculosis; HIV; Lymphoma